Sensorimotor Modulation Differs with Load Type during Constant Finger Force or Position - Kirimoto, Hikari (Public Library of Science, 2014)
During submaximal isometric contraction, there are two different load types: production of a constant force against a rigid restraint (force task), and maintenance of position against a constant load (position task). Previous studies reported that the time to task failure during a fatigue task was twice as long in the force task compared with the position task. Sensory feedback processing may contribute to these differences. The purpose of the current study was to determine the influence of load types during static muscle contraction tasks on the gating effect, i.e., attenuation of somatosensory-evoked potentials (SEPs) and the cortical silent period (cSP). Ten healthy subjects contracted their right first dorsal interosseus muscle by abducting their index finger for 90 s, to produce a constant force against a rigid restraint that was 20% of the maximum voluntary contraction (force task), or to maintain a constant position with 10° abduction of the metacarpophalangeal joint against the same load (position task). Somatosensory evoked potentials (SEPs) were recorded from C3′ by stimulating either the right ulnar or median nerve at the wrist while maintaining contraction. The cortical silent period (cSP) was also elicited by transcranial magnetic stimulation. Reduction of the amplitude of the P45 component of SEPs was significantly larger during the position task than during the force task and under control rest conditions when the ulnar nerve, but not the median nerve, was stimulated. The position task had a significantly shorter cSP duration than the force task. These results suggest the need for more proprioceptive information during the position task than the force task. The shorter duration of the cSP during the position task may be attributable to larger amplitude of heteronymous short latency reflexes. Sensorimotor modulations may differ with load type during constant finger force or position tasks.